Perancangan Aplikasi Informasi Cuaca Berbasis Android Menggunakan API dan JSON - Glenn Natanael Sofian; Wahyu Kusuma Raharja; Jalinas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Weather conditions are an inseparable part of human life. Weather conditions are very important and can affect daily activities. Weather conditions are also different in an area / city around the world. This study aims to produce weather information applications in an area / city around the world. This research was conducted with the steps of the waterfall method, planning in the form of pictures and weather information in accordance with OpenWeatherMap data information, needs analysis in the form of functional requirements and non-functional requirements, navigation structure design, use case diagrams, and user interfaces, programming with coding and implementation of the application interface, testing using variations of the Android operating system version and testing the user acceptance test (UAT). This research succeeded in building a weather information application with the name WeatherApp.apk measuring 3.3 MB and embedded with API and JSON. This application is composed of a home menu, finding city, and a splashscreen. Based on the blackbox test results, the WeatherApp.apk application can run on six versions of the Android operating system, namely, Android 5.1.1 (Lollipop), Android 6.0.1 (Marshmallow), Android 8.1.0 (Oreo), Android 11 (R), Android 10 (Q), Android 9.0 (Pie), Based on the user acceptance test (UAT) using a questionnaire to 10 respondents, and processed with a linkert scale, the results obtained are 86.67% in terms of appearance, 85% in terms of user convenience, and 87 ,5% in terms of benefits.